Suppose x and y satisfy the equations x 2 − y 2 4 = − 1 and x 6 + y 3 3 = 2 . Find the product x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great approach!
The change of variables allow us to convert this into a typical system of linear equations, which we can then solve.
Thank you very much Ivan! LOL
Let x 1 = a and y 1 = b , then:
2 a − 2 4 b = − 1 ...( i )
6 a + 3 3 b = 2 ...( ii )
Eliminate ( i ) with ( ii )
2 a − 2 4 b = − 1 | × 3
6 a + 3 3 b = 2 | × 1
6 a − 7 2 b = − 3
6 a + 3 3 b = 2
− 1 0 5 b = − 5
b = 2 1 1 ( remember b = y 1 )
y 1 = 2 1 1
y = 2 1
Substitute the value of b to ( i )
2 a − 2 4 b = − 1
2 a − ( 2 4 × 2 1 1 ) = − 1
2 a − 7 8 = − 1
2 a = − 1 + 7 8
2 a = 7 1
a = 1 4 1 ( remember a = x 1 )
x 1 = 1 4 1
x = 1 4
So, x y = 1 4 × 2 1 = 2 9 4
Multiply equation A by 3, so that both equations have the term 6/x.
Next, take both equations and subtract them from each other. Order doesn't matter. Then, solve for y. Once you have y, solve for x. It is 14 and 21.
Let's work with the first equation first,
x 2 − y 2 4 = − 1 ⟹ x y 2 y − 2 4 x = − 1 ⟹ 2 y − 2 4 x = − x y
⟹ 2 y + x y = 2 4 x ⟹ y ( 2 + x ) = 2 4 x ⟹ y = 2 + x 2 4 x
Now, let's substitute the value of y to the second equation,
x 6 + y 3 3 = 2 ⟹ x 6 + 2 + x 2 4 x 3 3 = 2 ⟹ x 6 + 2 4 x 6 6 + 3 3 x = 2 ⟹ 2 4 x 1 4 4 + 6 6 + 3 3 x = 2
⟹ 2 1 0 + 3 3 x = 4 8 x ⟹ 1 5 x = 2 1 0 ⟹ x = 1 4
Next, let's again substitute the value of x in the equation y = 2 + x 2 4 x ,
y = 2 + x 2 4 x ⟹ y = 2 + 1 4 2 4 × 1 4 ⟹ y = 1 6 3 3 6 ⟹ y = 2 1
Hence, the product x y is, 1 4 × 2 1 = 2 9 4
Therefore, the required answer is 2 9 4 ...
2/x=24/y-1 3.(2/x)+33/y=2 logo 3.(24/y-1)+33/y=2 então y=21 Como 2/x=24/21-1 implica que x=14 O produto x.y é 21 . 14 = 294
how the hell you people are able to solve like this
given 2/x-24/y=-1 & 6/x+33/y=2
2y-24x=-xy & 6y+33x=2xy
using simultaneous linear equations , we get:
6y-72x=-3xy - equation 1
6y+33x=2xy - equation 2
-105x=-5xy
=> y=21
substitute y in equation 2
6y+33x=2xy
=>126+33x=42x
=>9x=126
=>x=14
=>xy=21*14=294
required answer is 294
2y-24x=-xy (*-3) 6y+33x=2xy
72x+33x=5xy 105x=5xy y=21 x=2y/(24-y) => x=14 x*y = 294
Let us multiply by xy. As a result, we get the equations 2 y − 2 4 x = − x y and 6 y + 3 3 x = 2 x y . Adding these up, we have x y = 9 x + 8 y . Let's substitute this in for xy. So
2 4 x − 2 y = 8 y + 9 x
1 5 x = 1 0 y
x = 3 2 y
Substituting this back in, we get
1 6 y − 2 y = x y
y ( 1 4 − x ) = 0
x = 1 4 y = 2 1 .
nice one ;)
From equation 1, xy = 24x - 2y (3) From equation 2, 2xy = 33x + 6y (4)
From equation 3 and 4, x = 2/3*y
then from equation 3, y = 21 So, x = 2/3 * 21 = 14
Therefore, xy = 14 * 21 = 294
first make a straight simple equations as 2y-24x=-xy and 6y+33x=2xy then solve them to find either x or y. And substitute the value of a n unknown variable in either of the equation to find the other.Atlast find the product of x*y here x=42/3 and y=21,so xy=294 is the answer.
2y - 24x = - xy......(eq 1)
6y + 33x = 2xy... (eq 2)
6y + 33x = 2(-2y + 24x)
6y + 33x = -4y + 48x
10y = 15x
x = (10/15) y
x = (2/3)y
and then subs x to eq (1),so :
2y - 24 (2/3)y = -(2/3)y . y
2y - 16y = - (2/3) y^2
-14y = - (2/3) y^2
14(3/2) = y
y = 21
so that x = (2/3) 21 = 14
the result is xy = (14) (21) = 294
I used elimination. 2/x - 24/y = -1 6/x + 33/y = 2 You have to equate the numerator numbers. So, I mutiply 2/x - 24/y = -1 with 3. It became 6x - 72/y = -3, it's similar with 6/x + 33/y = 2. (used X for elimination).
evaluate (6/x - 72/y = -3) - (6x + 33/y = 2) . The result is y=21. distribute coefficient of y or 21 to 6/x + 33/y = 2 became 6/x + 33/21 = 2 you must transfer 33/21 to right, 6/x = 2 - 33/21. You have to equate the denominator number. 6/x = 2-3321 6/x = (42-33)/21 6/x = 9/21 x = 14 Finally, x = 14 and y = 21, so xy =294
how to solve simultaneous equation?? i have try but still can't answer the question.. would you helped me? :)
This is a quote of course nur :) in elimination, you just vave to equate the numerator, not denominator.
This is a quote In this, I'll be equate the coefficient of X.
2/X - 24/Y = -1 || x3 (mutiply with 3) 6/X + 33/Y = 2 || x1 (mutiply with 1)
This is a quote so, it's became a same coefficient of X.
|| 6/X - 72/Y = -3 || 6/X + 33/Y = 2 ||
This is a quote reduce both statement
0 - 105/Y = -5
-105/-5 = Y
Y = 21
This is a quote If you have found Y, distribute Y to statement, dont both! just one.
2/X - 24/Y = -1 or 6X + 33/Y = 2 But I chose 6X + 33/Y = 2
This is a quote So, change Y with 21
6X + 33/21 =2 |
|| 6/X = 2 - 33/21 || || 6/X = (42-33)/21 || || 6/X = 9/21 || 6/X = 3/7 || cross mutiplied to get X
3X = 42
X = 14
This is a quote Finished, you should evaluate XY, and the answer is ... 14 * 21 = 294
BY SOLVING THE GIVEN EQUATIONS WE FIND X AND Y WHICH AR X=14 AND Y=21 AND THEN XY=294
You should state how you solved the equations, so that others can learn from what you did.
Simply giving the numerical value is not helpful.
2 / x − 2 4 / y = − 1 ....... i
6 / x + 3 3 / y = 2 ........ii
i ∗ 3 => 6 / x − 7 2 / y = − 3 ....a
i i ∗ 1 => 6 / x + 3 3 / y = 2 .....b
a − b => − 7 2 / y − 3 3 / y = − 3 − 2 => − 1 0 5 / y = − 5 => 1 0 5 = 5 y => 2 1 = y
Putting the value of y in the 1st equation => 2 / x − 2 4 / 2 1 = − 1 => 2 / x = 8 / 7 − 1 => 2 / x = 1 / 7 => 1 4 = x
And xy = 2 1 ∗ 1 4 = 2 9 4
make a system you will found 6/x= 72/y -3 after this 72/y-3 + 33/y = 2 y =21
2/x- 24/22= -1 x=14
Please note that this solution only works because the variables were non-zero. All sorts of strange results can be produced by dividing by zero.
Clear the fractions by multiplying both equations by xy . This yields the following system of equations
2y - 24x = -xy
6y + 33x = 2xy
Solve either equation for either variable. I solved the first equation for y.
y = 12x - 2 x y
Substitute this value into the other equation.
6(12x - 2 x y ) + 33x = 2xy
Simplify
72x - 3xy + 33x = 2xy
105x -3xy = 2xy
105x = 5xy
105 = 5y (This is where you have to know that x is non-zero)
21 = y
Substitute this value for y into any of the above equations and solve for x.
21 = 12x - 2 2 1 x
42 = 24x - 21x
42 = 3x
14 = x
Now find the product of x and y and you're done.
Multiplicando ambas as equações por \( xy \), temos: \( 2 y - 24 x = - xy\) e \( 6 y + 33 y = 2xy (I)\). Multiplicando a primeira por \( -3 \), temos \( -6 y + 72 x = + 3xy (II) \). Somando \( (I) \) e \( (II) \), chegamos em 1 0 5 x = 5 x y de onde chegamos em y = 2 1 . Substituindo na primeira equação, chegamos em \( x = 14.\). Portanto, \( x \times y = 294\).
Problem Loading...
Note Loading...
Set Loading...
Let us assume that x 1 = m and y 1 = n . Therefore, it is evident that 2 m − 2 4 n = − 1 and 6 m + 3 3 n = 2 . Furthermore, we get the system
{ 2 m − 2 4 n = − 1 6 m + 3 3 n = 2
whose solutions are m = 1 4 1 and n = 2 1 1 , meaning that x = 1 4 and y = 2 1 . Thus, the product x y = 2 9 4 .